Pengaruh Sosial Media Terhadap Kesadaran Perawatan Anak pada Remaja Putri di Kecamatan Cilandak Timur - Badruddin, Syamsiah; -, Tasya (Jurnal Ilmiah Publika, 2022)
Social media makes a new part of life for humans in expressing themselves and is a need for everyone. It is undeniable that social media has a tremendous influence on people's lives, especially for teenagers. Social media has its own power in attracting attention, with the existence of social media, people can socialize easily. Social media also gives rise to technological crimes, namely child grooming. Although child grooming is a new crime that occurs in Indonesia. Therefore, the researcher wanted to see the effect of social media on child grooming. This study used a descriptive quantitative method. Teenage girls aged 10-14 years were respondents in this study. This research uses functional structural theory and social facts. Based on the results of the analysis obtained in this study, namely that there is an influence of social media on child grooming.